Pengaruh Pelatihan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai UPT Pelatihan Kehutanan dan Pemberdayaan Masyarakat Provinsi Riau - Barza, Panzi; Sari, Novita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
purpose of this study was to determine the effect of job training and work motivation on employee performance at the Pekanbaru Forestry Training Office. The sample in this study was 44 employees of the Pekanbaru Forestry Training Office. The variables studied in this study were job training (X1), work motivation (X2), and employee performance (Y). The data analysis used multiple regression methods using validation tests, reliability tests, multiple linear regression tests, classical assumption tests, normality tests, multicollinearity tests, partial tests (t-tests), and determinant coefficients (R2). The test was carried out in order to determine the effect of independent variables (independent) and dependent variables. Based on the results of the study, job training (X1), work motivation (X2), and have an effect on employee performance (Y) with an R value of 0.601 which indicates a positive relationship between job training (X1), work motivation (X2), and employee performance (Y) at the Pekanbaru Forestry Training Office. While R square is obtained as much as 0.61 which indicates a positive relationship direction between job training (X1), work motivation (X2), and employee performance (Y) at the Pekanbaru forestry training office. Partially obtained job training (X1), work motivation (X2) have a positive and significant effect on employee performance (Y) at the Pekanbaru forestry training office with a significance of 0.001 smaller than 0.05 multiple linear regression equation as follows: Y = 1.749 + 0.347 Job Training + 0.526 Work Motivation.